Neonatal Episodic Laryngospasm Treated with Sodium Channel Blockers - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Three male neonates with episodic laryngospasms responsive to sodium channel blockers are reported by researchers at centres in Lyon, Paris and Rennes, France.